STRENGTHENING PHASES OF CAST-IRON PARTS OF GLASS-MOLDS WITH GRADIENT STRUCTURE OF MOLDING - I. O. Leushin; Yu. A. Zinovyev; D. G. Chistyakov (Литьë и металлургия)
The process of production of cast blanks of cast-iron glass-molds is considered. Influence of various structural components on firmness of molding sets is described. Impact of hardening phases on behavior of the glass-molds elements and increase of reliability of their operation is investigated.